2007
DOI: 10.4067/s0717-66432007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Banco De Semillas, Regeneracion Y Crecimiento De Teline Monspessulana (L.) K. Koch Despues De Un Incendio Forestal

Abstract: RESUMENLas especies de plantas invasoras y el fuego pueden generar retroalimentación positiva, modificando la dinámica del paisaje y los ciclos ecosistémicos. Este trabajo tiene por objetivo estudiar los patrones poblacionales de Teline monspessulana después de un incendio forestal en la zona costera de la Región del Bío-Bío, Chile, dominada por plantaciones forestales de Pinus radiata y Eucalyptus globulus. El estudio se realizó en un sector del Cerro Caracol, adyacente a la ciudad de Concepción, que fue afec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…pers.) y resistencia y viabilidad por largos periodos de tiempo (García et al, 2007). Esta especie presenta tasas de regeneración altas, a través de renuevos vegetativos o a partir de semillas (Barrera et al, 2010), que permite la formación de un banco de semillas abundante y persistente en el tiempo a la espera de la ocurrencia de un disturbio para su activación y recolonización.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…pers.) y resistencia y viabilidad por largos periodos de tiempo (García et al, 2007). Esta especie presenta tasas de regeneración altas, a través de renuevos vegetativos o a partir de semillas (Barrera et al, 2010), que permite la formación de un banco de semillas abundante y persistente en el tiempo a la espera de la ocurrencia de un disturbio para su activación y recolonización.…”
Section: Discussionunclassified
“…En el trópico, la especie coloniza diferentes ecosistemas, encontrándo-se bajo coberturas arbóreas, en áreas abiertas de talud, en claros de bosque y asociada a matrices de pastizales con suelos pobres en nutrientes o deficiencias hídricas (Bohórquez, 2013). En esos sitios G. monspessulana forma matorrales densos que incrementan el riesgo para la generación y propagación de incendios y excluyen especies nativas provocando una disminución en la biodiversidad (García et al, 2007;Pauchard et al, 2008). Esto limita la sostenibilidad de las áreas conservadas, por lo que es necesario controlar sus poblaciones para lograr los objetivos de restauración ecológica (Gutiérrez, 2006).…”
Section: Introductionunclassified
“…These perturbations cause the replacement of older plants with new plants from the soil seed bank (García et al 2010), generating an even-age structure within populations. The rapid growth of the species produces plants close to 1 m in height only a few months after germination (García et al 2007), which then reach an average height of 2.7 m by the adult stage (, 6 years). This rapid growth leads to extensive intraspecific competition that is reflected in marked mortality in populations, with densities decreasing from 300 to 15 plants m À2 in less than a decade.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to modifying fire regimes, T. monspessulana may also benefit from wildfires (García et al 2010). T. monspessulana regenerates abundantly from the seed bank after a wildfire (García et al 2007;Pauchard et al 2008) and shows rapid growth in height during the following months (García et al 2007). The seeds of this species are able to withstand high temperatures in the soil seed bank during fires (Alexander and D'Antonio 2003b;García et al 2010), and seed germination for this species has been shown to increase with increasing temperatures, reaching its maximum when seeds were preheated to between 80 and 1208C (García et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, fires have further promoted the invasion by Monterey pines in areas of severely burnt native forests. If these events increase in frequency due to global warming [79,80], an additional pressure on native forests will come from invasion (and eventual replacement) by fire tolerant exotic species [81]. Because of the latter, calls have been made to reduce the cover of industrial forests.…”
Section: Conservation Implicationsmentioning
confidence: 99%